Cyfres Yr Onnen - Wyn, Rhiannon (Y Lolfa, 2009)
Erin has recently moved into a smart old mansion which is featured on the TV programme 'Dy Dŷ' ('Your House'). The presenter, Robyn Rici, and Sara, Erin's mother, develop a relationship. But little do they know that Erin also has a friend. Madam Petra wants to make sure that Erin has fair play, in school and at home. The winner of the Tir. Intro – PENNOD 1 – PENNOD 2 – PENNOD 3 – PENNOD 4 – PENNOD 5 – PENNOD 6 – PENNOD 7 – PENNOD 8 – PENNOD 9 – PENNOD 10 – PENNOD 11 – PENNOD 12 – PENNOD 13 – PENNOD 14 – PENNOD 15 – PENNOD 16 – PENNOD 17 – PENNOD 18 – PENNOD 19 – PENNOD 20.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books